A contemporary approach to body mass regulation mechanisms - Nowak, Andrzej; Czkwianianc, Elżbieta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Recently, a lot of factors and mechanisms regulating body mass have been discovered, although there are still many unknowns. Their effect on the development of many diseases related to nutritional disorders (obesity, anorexia, celiac disease, inflammatory bowel disease) means that the understanding of these mechanisms will make it possible to determine new therapeutic goals and create new medicinal products. This is even more important because nowadays there is no effective medication to cure nutritional disorders. It is necessary to conduct further research to evaluate dependencies and relationships between particular hormones and to study newly discovered substances so that we could progress towards achieving the overall objectives while keeping the ultimate goals in mind.